The gender enrolment gap in foreign language education revisited: Contemporary issues in a Ghanaian higher education institution - Lomotey, Benedicta Adokarley; Csajbok-Twerefou, Ildiko; Husein, Alhassan Abdur-Rahim; Diabah, Grace (System (Linköping), 2023)
This paper investigates the intersection between gender and foreign language education with specific reference to subject choice, motivation, and achievement. The study was carried out at a Ghanaian public university, amongst students of the following Bachelor of Arts foreign language programmes: Arabic, Chinese, French, Kiswahili, Russian and Spanish. Through a thematic analysis of transcribed focus group discussions and desk-research of relevant administrative documents, the authors inquire why a gender enrolment gap exists in the foreign language programmes and if indeed, certain languages are perceived as more masculine than others. The findings of the study confirm the existence of a gender gap in foreign language education. Participants also considered some languages such as Spanish and French as more feminine. Regarding their motivation, participants noted both integrative and instrumental factors that motivated them to study the foreign language. Additionally, the study found no statistical significance between the performance of females and males. However, males performed slightly better than females in Arabic, French, Kiswahili and Russian whereas females performed better in Spanish and Chinese.